Westonci.ca is the premier destination for reliable answers to your questions, brought to you by a community of experts. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
Certainly! Let's solve the system of equations using the substitution method step-by-step. The system of equations provided is:
[tex]\[ \begin{cases} 3x + 2y = -9 & \quad (1) \\ x = y + 7 & \quad (2) \end{cases} \][/tex]
### Step 1: Solve one of the equations for one variable
Equation (2) is already solved for [tex]\(x\)[/tex]:
[tex]\[ x = y + 7 \][/tex]
### Step 2: Substitute this expression into the other equation
We will substitute [tex]\(x = y + 7\)[/tex] into equation (1):
[tex]\[ 3(y + 7) + 2y = -9 \][/tex]
### Step 3: Simplify the resulting equation
First, distribute the 3 on the left side:
[tex]\[ 3y + 21 + 2y = -9 \][/tex]
Combine like terms:
[tex]\[ 5y + 21 = -9 \][/tex]
### Step 4: Solve for [tex]\(y\)[/tex]
Subtract 21 from both sides to isolate the [tex]\(y\)[/tex] term:
[tex]\[ 5y = -9 - 21 \][/tex]
[tex]\[ 5y = -30 \][/tex]
Divide both sides by 5:
[tex]\[ y = -6 \][/tex]
### Step 5: Substitute [tex]\(y\)[/tex] back into the expression for [tex]\(x\)[/tex]
We found [tex]\(y = -6\)[/tex]. Substitute this value into the expression [tex]\(x = y + 7\)[/tex]:
[tex]\[ x = -6 + 7 \][/tex]
[tex]\[ x = 1 \][/tex]
### Conclusion
The solution to the system of equations is:
[tex]\[ (x, y) = (1, -6) \][/tex]
So, the values of [tex]\(x\)[/tex] and [tex]\(y\)[/tex] are:
[tex]\[ x = 1, \quad y = -6 \][/tex]
[tex]\[ \begin{cases} 3x + 2y = -9 & \quad (1) \\ x = y + 7 & \quad (2) \end{cases} \][/tex]
### Step 1: Solve one of the equations for one variable
Equation (2) is already solved for [tex]\(x\)[/tex]:
[tex]\[ x = y + 7 \][/tex]
### Step 2: Substitute this expression into the other equation
We will substitute [tex]\(x = y + 7\)[/tex] into equation (1):
[tex]\[ 3(y + 7) + 2y = -9 \][/tex]
### Step 3: Simplify the resulting equation
First, distribute the 3 on the left side:
[tex]\[ 3y + 21 + 2y = -9 \][/tex]
Combine like terms:
[tex]\[ 5y + 21 = -9 \][/tex]
### Step 4: Solve for [tex]\(y\)[/tex]
Subtract 21 from both sides to isolate the [tex]\(y\)[/tex] term:
[tex]\[ 5y = -9 - 21 \][/tex]
[tex]\[ 5y = -30 \][/tex]
Divide both sides by 5:
[tex]\[ y = -6 \][/tex]
### Step 5: Substitute [tex]\(y\)[/tex] back into the expression for [tex]\(x\)[/tex]
We found [tex]\(y = -6\)[/tex]. Substitute this value into the expression [tex]\(x = y + 7\)[/tex]:
[tex]\[ x = -6 + 7 \][/tex]
[tex]\[ x = 1 \][/tex]
### Conclusion
The solution to the system of equations is:
[tex]\[ (x, y) = (1, -6) \][/tex]
So, the values of [tex]\(x\)[/tex] and [tex]\(y\)[/tex] are:
[tex]\[ x = 1, \quad y = -6 \][/tex]
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.